Ewing’s Sarcoma: imaging findings of a patient with primary tumor in the femur and mandibular metastasis - AMARAL,Fabrício Rezende (2018)
ABSTRACT Ewing’s Sarcoma, a common primary bone malignancy that usually occurs in childhood and young adults, has a predilection for males and occurs mostly in the diaphysis of long bones and pelvis. This tumor rarely affects the head and neck. Histologically, this neoplasm is a small round cell tumor and there is evidence of a neuroectodermal origin. Radiographic findings of ES show an osteolytic lesion, that is not a pathognomonic feature for this neoplasm. The association of conventional imaging methods such radiography, Computed Tomograph (CT), magnetic resonance imaging (MRI), combined with scintigraphy or Positron Emission Tomography/ Computed tomography PET /CT), is essential for a correct diagnosis and treatment. Therefore, the aim of this report was to present image findings of a patient who presented with ES in the femur, and a metastasis in the mandible after eighteen months, and discuss the importance of imaging methods for a correct diagnosis, treatment and consequently, prognosis.